The balance between apoptosis and autophagy regulates testis regression and recrudescence in the seasonal-breeding South American plains vizcacha, Lagostomus maximus - González, Candela R. (PLoS One, 2018)
Mammalian testis undergoes deep changes in their architecture and function during photoregression conditions in seasonal breeders. Particularly, the testicular mechanisms that regulate the transition between the active (functional) and inactive (regression) stage vary between species. The aim of the present study was to analyze the incidence of proliferation, apoptosis and autophagy in the testicular seminiferous ephitelium of a seasonal breeder, Lagostomus maximus, during the annual reproductive cycle. We observed that proliferating spermatogonia increased from the active testis until reaching the maximum peak in the activating testis. During the annual reproductive cycle, the quantity of apoptotic-TUNEL positive spermatogonia and meiotic germ cells was constant and this might be regulated by the members of the BCL2 family. Only in the activating testis, apoptosis of germ cells was almost undetectable. The analysis of the autophagic-related proteins BECN1 and LC3 showed their localization in Leydig cells and the germ cells in the active and activating testis. In the inactive testis, BECN1 and LC3 ceased to be immunolocalized within the seminiferous tubules and the mRNA expression of both regulators decreased. Moreover, the expression of BECN1 and LC3 and also the apoptotic index were up regulated in testicular cultures subjected to nutritional stress. These results suggest a possible interaction between apoptosis and autophagy in the active and activating testis (characterized by high metabolic requirement and nutrient), where autophagy could promote survival over cell death. In the inactive testis, the absence of autophagic-related proteins might explain the massive loss of germ cells, suggesting that autophagy plays new and key role in the alterations of the seminiferous epithelium during photoregression.